CHALLENGES IN INTERPRETING ENGLISH INTO INDONESIAN BY INDONESIAN INTERPRETERS - Hulu, Fasaaro; Ambalegin, Ambalegin (IdeBahasa, 2024)
TThis study aims to discover the challenges in interpreting English into Indonesian. When the the source language (SL) speaker delivers a speech, and interpreters convey the meaning into the Indonesian language as target language (TL). This study used qualitative research method. Data were collected by using the interview, open-ended questions to obtain main data from the respondents. Respondents are Indonesian interpreters in Indonesia as they have more than five years of experience in interpreting. The collected data are transcribed and deeply analyzed, grouped and compared with the different and similar data to recent research results, explained by using words and texts and applied a table to display the results of challenges English in interpreting. The results of this research indicate the challenges English in interpreting. First, the most challenging faced by interpreters is long talks. Second, the lack of pronunciation is more challenging to record all words pronounced from the speech. And the third, topic mastery is the basic challenging as the source of materials are not available and there is not much time to approach the speakers’ source language (SL).